Do donors get what they paid for? : micro evidence on the fungibility of development project aid - Van de Walle, Dominique, 1956- 1956- (Policy research working paper, 2005)
"Recipient government responses to development project aid have typically been studied at high levels of aggregation, using cross-country comparisons and/or aggregate time series data. Yet increasingly the relevant decisions are being made at the local level, in response to specific community-level projects. The authors use local-level data to test for fungibility of World Bank financing of rural road rehabilitation targeted to specific geographic areas of Vietnam. A simple double difference estimate suggests that the project's net contribution to rehabilitated road increments is close to zero, suggesting complete displacement of funding. However, with better controls for the endogeneity of project placement the authors find much less evidence of fungibility, with displacement accounting for around one-third of the aid. The results point to the importance of dealing with selection bias in assessing project aid fungibility. "--World Bank web site